The Disruption of a Gα Subunit Sheds New Light on the Pathogenicity of Stagonospora nodorum on Wheat - Solomon, P.; Tan, Kar-Chun; Sanchez, P.; Cooper, R.; Oliver, Richard (2004)
Gna1, a gene encoding a Gα subunit, a key component of signal transduction pathways, has been cloned and characterized in the wheat pathogen Stagonospora nodorum. Analysis of Gna1 expression during infection revealed a slight decrease in transcript levels shortly after germination, after which levels steadily increased until sporulation. Inactivation of Gna1 had a pleiotropic effect on phenotype. The Gna1 mutants were less pathogenic, attributed to coinciding with a defect in direct penetration. Also, Gna1 mutants were unable to sporulate, showed an albino phenotype, and secreted one or more brown pigments into growth media. Analysis of growth medium identified tyrosine, phenylalanine, and dihydroxyphenylalanine (L-DOPA) were excreted by the gna1 strains but not by wild type. The presence of these compounds, and the insensitivity of melanization to tricyclazole suggest that S. nodorum synthesizes melanin via the L-DOPA pathway, the first fungal phytopathogen described to do so. Decreases in protease (and several other depolymerases) activities and sensitivity to osmotic stress were other phenotypes identified in the Gna1 mutants. Gna1 is the first signal transduction gene to be cloned and characterized from S. nodorum and its inactivation has uncovered several previously unknown facets of pathogenicity.